1976
DOI: 10.1002/app.1976.070200708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler on the relaxation time spectra of filled polymers

Abstract: The temperature and frequency dependences of the complex shear modulus G* and tan δ of mechanical losses of epoxy compositions with various fillers were studied. The method of Ninomiya‐Ferry applied to the reduced curves of frequency dependence of the effective part of the shear modulus was used to draw up relaxation time spectra for specimens with various concentrations of the filler. Regularities in the change of type and position of the spectral curves with increase in filler concentration were indicated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Moreover, T~-values are influenced by the conditions of de'formation of the polymer, which exist between fillers, and the restriction in the molecular mobility due to absorption-interaction in polymer-surface layers of the filler (17).…”
Section: B Dynamic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, T~-values are influenced by the conditions of de'formation of the polymer, which exist between fillers, and the restriction in the molecular mobility due to absorption-interaction in polymer-surface layers of the filler (17).…”
Section: B Dynamic Measurementsmentioning
confidence: 99%
“…It was found that glassresin composites are affected by absorbed moisture for whatever type of bonding, existing at the interface (16). Finally, a main reason for the alternation in the type and position of the spectral curves is the changes in the conditions of deformations of the polymer between fillers and the restriction in the molecular mobility due to absorption interaction in polymer surface layers onto filler (17).…”
mentioning
confidence: 99%
“…NMR techniques (7), and dynamic mechanical spectrometry (4, 8-1 1). Thus, Lipatov and co-workers (10,11) have shown a widening of the relaxation time spectra, for various particulate composites as PS, PMMA, and epoxy. This was attributed to both a decrease in the flexibility of macromolecular chains in the surface layer and interactions of chains with the fillers.…”
Section: Introductionmentioning
confidence: 97%
“…The presence of filler actually restricts the segmental and molecular mobility of the polymeric matrix, as adsorption interaction in polymer surface layers onto filler particles occurs (6). It is obvious that under these conditions, the quality of adhesion can hardly be quantified and a more thorough investigation is necessary.…”
Section: Introductionmentioning
confidence: 99%